Penerapan ISAK 35 terhadap Laporan Keuangan Masjid Studi Kasus di Masjid An Nuur Tulungagung - Fredy Setiawan; Agus Eko Sujianto; Angga Widyawardana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the application of ISAK 35 to the financial reports of the An Nuur Mosque in Tulungagung. ISAK 35, as part of sharia-based Financial Accounting Standards, has the aim of ensuring compliance with sharia accounting practices in the management of funds and assets. The An Nuur Mosque was chosen as a case study because of its central role in providing religious and social services in the Tulungagung community. This research involves an in-depth analysis of the An Nuur Mosque's financial reports, focusing on elements related to ISAK 35, such as recording sharia-based transactions, separating amil and zakat funds, as well as disclosing information in accordance with sharia principles. The case study method is used to understand the implementation of ISAK 35 in a practical context and gain a holistic understanding of mosque financial management. The research results are expected to provide a deeper understanding of the extent to which the An Nuur Mosque has complied with ISAK 35 and its impact on transparency, accountability and public trust. The implications of this research can also provide insight for financial managers of mosques and sharia financial institutions to increase efficiency and compliance in managing religious funds. Through this research, it is hoped that practical recommendations will emerge to improve the application of ISAK 35 in mosque financial reports, with the ultimate aim of strengthening the financial integrity and sustainability of mosques as religious institutions. Thus, this research makes a positive contribution to the development of sharia accounting practices in the context of mosque finances in Indonesia